Guidelines for laboratory analyses for poisoned patients in the United Kingdom. (May 2014) - Thompson, JP; Watson, ID; Thanacoody, HKR; Morley, S; Thomas, SHL; Eddleston, M; Vale, JA; Bateman, DN; Krishna, CV
To enable consistency of investigation and the establishment of best practice standards, consensus guidelines were formulated previously by the UK National Poisons Information Service and the Association for Clinical Biochemistry. These joint guidelines have now been updated to reflect current best practice. The types of laboratory investigation required for poisoned patients are categorized as either (a) essential common laboratory investigations or (b) specific toxicological assays, and also as either (i) common or (ii) specialist or infrequent. Tests in categories (a) and (bi) should be available 24 hours per day, with a maximum turnaround time of 2 h. For the specialist assays, i.e. category (bii), availability and turnaround times have been specified individually. The basis for selection of these times has been clinical utility. The adoption of these guidelines, along with the use of the National Poisons Information Service (0844 8920111) and its online poisons information resource TOXBASE® (www.toxbase.org ) enable the poisoned patient to receive appropriate, 'best practice' investigations according to their clinical needs and will avoid unnecessary investigations.